Controlled release of C-type natriuretic peptide by microencapsulation dampens proinflammatory effects induced by IL-1 beta in cartilage explants - Peake, N.J.; Pavlov, A.M.; D'Souza, A.; Pingguan-Murphy, Belinda; Sukhorukov, G.B.; Hobbs, A.J.; Chowdhury, T.T. (2015)
C-type natriuretic peptide (CNP) exhibits potent anti-inflammatory effects in chondrocytes that have the potential to repair cartilage damage observed in osteoarthritis (OA). However, treatments for OA have been challenging due to poor targeting and delivery of therapeutics. The present study fabricated polyelectrolyte microcapsules loaded with CNP and examined whether the layer-by-layer (LbL) approach could have protective effects in cartilage explants treated with the pro-inflammatory cytokine, interleukin-1 beta (IL-1 beta). SEM showed uniform, 2 to 3 mu m spherical microcapsules with morphological characteristic similar to templates loaded with or without CNP. The protein was localized around the external surface of the microcapsules with encapsulation efficiencies >82.9. CNP release profiles were broadly similar following 9 days of culture. The presence of CNP microcapsules did not significantly affect cell viability (80) with DNA values that remained stable throughout the culture conditions. Confocal imaging showed clustering of microcapsules in chondrocytes to natriuretic peptide receptor (Npr) 2 and 3. Treatment of cartilage explants with CNP microcapsules led to concentration-dependent inhibition of NO release in response to IL-1 beta and restoration of matrix synthesis. In summary, we demonstrate controlled delivery of CNP to dampen pro-inflammatory effects induced by IL-1 beta in cartilage explants. The LbL approach has the potential to promote cartilage repair in vivo.